KENASABAN FOSFAT SERUM, C-REAKTIF PROTEIN DAN FETUIN A DI PASIEN GINJAL TAHAP AKHIR DENGAN HEMODIALISIS - KS, Indranila; Winarto, Heri; AP, Purwanto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2016)
Patients with end-stage renal disease (ESRD) who undergo hemodialysis have chronic inflammation caused by several factors,including biocompatibility of dialyzer membran. Inflammation will decrease the fetuin A level in serum. The elevation of the markerinflammation (CRP), hyperphosphatemia and decrease of fetuin A level are the risk faktors for vascular calcification. The aim of thisstudy was to know the relationship between serum phosphate, CRP and fetuin A levels in ESRD patients who underwent hemodialysis. Theresearch was carried out by observational cross sectional analytical approach with consecutive sampling on 31 ESRD patients undergoingchronic hemodialysis in the Hemodialysis Unit of the Dr.Kariadi Hospital, by examining levels of CRP by ELISA, serum phosphate byPhosphomolibdate methods and fetuin A by ELISA. The relationships between phosphate serum and CRP, CRP and fetuin A, phosphateserum and fetuin A were analyzed using Spearman correlation test. In this study it was found that 100% of subjects had CRP levels >0.3mg/dL (reference range 0.1-0.3 mg/dL); 61.3% of subjects had serum phosphate >5.1 mg/dL (reference range 2.5-5.1 mg/dL) and allsubjects (100%) had fetuin A levels <0.5 ng/mL (reference range 0.5-1 ng/mL). There was a moderate positive significant correlationbetween serum phosphate and CRP (p=0.024 and r=0.404), there was a strong negative significant correlation between CRP and fetuinA (p=0.000 and r=-0.628). No significant correlation between the phosphate serum and fetuin A (p=0.365 and r=-0.168) was found.Based on this study, it was found that the higher serum phosphate level resulted in a higher CRP and lower fetuin A.